2008
DOI: 10.1007/s11666-008-9271-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of WC-Co Coatings Deposited by Warm Spray Process

Abstract: The high-velocity oxy-fuel (HVOF) process is commonly used to deposit WC-Co coatings. There are some problems with this process; especially the decomposition and decarburization of WC during spraying make a coating brittle. To suppress such degradation, the warm spray (WS) process was applied to deposit WC-Co coatings, which is capable of controlling the flame temperature in the range of 500-2000°C. The microstructure and phases of the deposited coatings were characterized by using SEM and XRD, and the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…Many studies have shown the effects of these phases on the properties of the coatings (Ref 3 -7). Many efforts, therefore, have been made to deposit WC-Co coating in lower temperature ranges than those of HVOF process to suppress the decarburization and decomposition of WC by using highvelocity air fuel (HVAF), cold spray, pulsed gas dynamic spraying (PGDS), and Warm spray (WS) processes (Ref [8][9][10][11][12][13][14][15]. These coatings show no/little detrimental phase transformation and decarburization of WC.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown the effects of these phases on the properties of the coatings (Ref 3 -7). Many efforts, therefore, have been made to deposit WC-Co coating in lower temperature ranges than those of HVOF process to suppress the decarburization and decomposition of WC by using highvelocity air fuel (HVAF), cold spray, pulsed gas dynamic spraying (PGDS), and Warm spray (WS) processes (Ref [8][9][10][11][12][13][14][15]. These coatings show no/little detrimental phase transformation and decarburization of WC.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been made to deposit WC-Co coating in lower temperature ranges than those of HVOF process in order to suppress decarburization and decomposition of WC phases by using high-velocity air fuel (HVAF), cold spray, pulsed gas dynamic spraying (PGDS), and Warm spray (WS) processes (Ref [8][9][10][11][12][13][14][15][16][17][18]. These coatings show no/little detrimental phase transformation and decarburization of WC.…”
Section: Introductionmentioning
confidence: 99%
“…Microstructure and mechanical properties of WS coatings have been investigated (Ref 4,(6)(7)(8)(9)12,15,17,19,20) for materials such as titanium, copper, aluminum, metallic glass, WC-Co cermet, nano-grain titanium oxide, UHMW-PE, and PEEK. Among them, titanium and WC-Co have been most extensively studied due to their potential application importance and sensitivity to thermal degradation.…”
Section: Microstructure and Mechanical Properties Of Ws Metallic Coatmentioning
confidence: 99%
“…Since the first papers on warm spraying (WS) were published in 2006 (Ref 1, 2), significant efforts have been made to understand its process fundamentals as well as to explore potential advantages of coatings made by the process for industrial applications (Ref [15][16][17][18][19][20]. Various thermal spray processes are classified schematically in terms of particlesÕ temperature and velocity on a so-called process map as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%